Odpowiedzi

2010-03-02T14:53:41+01:00
A).2*3+y=8
6+y=8
y=8-6
y=2

b).x-(-1)=6
x+1=6
x=6-1
x=4

c).3*4-2y=6
12-2y=6
12-6=2y
6=2y
2y=6//2
y=3



x+y=9
x-y=3

np.
x=6
y=3

6+3=9
6-3=3



mam nadzieję że jest dobrze :)))

1 5 1
Najlepsza Odpowiedź!
2010-03-02T14:54:30+01:00
A) 2*3+y = 8
6+y = 8
y = 8-6
y = 2

b) x - (-1) = 6
x + 1 = 6
x = 6 - 1
x = 5

c)3*4 - 2y = 6
12 - 2y = 6
2y = 12 - 6
2y = 6 |:2
y = 3

d)x + y = 9
x - y = 3
---------------
2x = 12 |:2
x = 6

6 + y = 9
y = 9 - 6
y = 3
2010-03-02T14:56:23+01:00
A) 2x+y=8
x=3
2*3+y=8
x=3
6+y=8
x=3
y=8-6
x=3
y=2
x=3

b)x-y=6
y=-1
x+1=6
y=-1
x=6-1
y=-1
x=5

c)3x-2y=6
x=4
3*4-2y=6
x=4
12-2y=6
x=4
2y=-12+6
x=4
2y=-6/2
x=4
y=-3

Mam nadzieje ze troche pomogłam:)
1 5 1